PENGEMBANGAN LARGE SIZE VERNIER CALIPER UNTUK PENGUKURAN BENDA DALAM KEHIDUPAN SEHARI-HARI - Fatiatun, Fatiatun; Naja, Farda NIhayan; Septyana, Ananda Lisa; Rakhmadhani, Annisa (AL-QALAM: JURNAL KEPENDIDIKAN, 2022)
The development of the large size vernier caliper was motivated by the limited use of the vernier caliper which has grown to a small size. A large size vernier caliper is one of the length measuring tools used to determine the inner, outer diameter, and depth of an object. The caliper that has been developed at this time can only be used to measure small objects. This study developed a long measuring instrument in the form of a large caliper with very simple manufacturing and experimental technique. In everyday life, many objects are large and cannot be measured with a caliper that is sold in the market. The principle of high precision and accuracy is applied in the manufacture of this measuring instrument because it greatly affects the results obtained. This caliper is suitable for use as a measuring tool for large objects..